2018
DOI: 10.1155/2018/7806873
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia in a Patient with Moyamoya Disease

Abstract: Moyamoya disease is a chronic progressive cerebrovascular disease characterized by bilateral occlusion or stenosis of arteries around circle of Willis. We report a case of 18-year-old female presented with recurrent episodes of headache and vertigo. On cerebral angiography, the patient was diagnosed to have moyamoya disease. On further evaluation, thrombophilia profile showed increased homocysteine level. The patient was treated conservatively with cobalamin and aspirin and advised for revascularization. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In patients from South China, the detection rate of MMD is 3.2% in patients undergoing cerebral angiography, yet we do not know the exact incidence of adult MMD. from case reports of MMD (bilateral or unilateral), in which homocysteine level was also noted to be a risk factor for MMD (5,23). Many retrospective and prospective studies have confirmed that hyperhomocysteinemia is a potential independent risk factor for atherosclerosis (22), and an increased homocysteine level has been reported to be an independent risk factor for cerebral atherosclerosis (2).…”
Section: █ Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In patients from South China, the detection rate of MMD is 3.2% in patients undergoing cerebral angiography, yet we do not know the exact incidence of adult MMD. from case reports of MMD (bilateral or unilateral), in which homocysteine level was also noted to be a risk factor for MMD (5,23). Many retrospective and prospective studies have confirmed that hyperhomocysteinemia is a potential independent risk factor for atherosclerosis (22), and an increased homocysteine level has been reported to be an independent risk factor for cerebral atherosclerosis (2).…”
Section: █ Discussionmentioning
confidence: 97%
“…A recent study indicated an association between two novel single-nucleotide polymorphisms in the gene regulating homocysteine metabolism (rs9651118 in MTHFR and rs117353193 in TCN2), resulting in increased homocysteine levels in patients with MMD (7,8). We believe that the genetic metabolic factor for homocysteinemia in the release of nitric oxide is the proposed mechanism (21), resulting in the development of moyamoya vessels and stroke (23).…”
Section: █ Discussionmentioning
confidence: 99%